Designing UI/UX for Web-Based Evaluation in Artificial Intelligence E-Learning to Determine Learning Motivation with Design Thinking Approach - Muhammad Zahid Tsaqif; Erna Piantari; Erlangga Erlangga (Universitas Pendidikan Indonesia, 2023)
E-Learning is a solution to increase knowledge and skills. One of them is learning Artificial Intelligence (AI). Based on this, AI can be learned through web-based e-learning, one of which is on the eCraft2Learn web. The eCraft2Learn website is an e-learning about AI that applies block-based programming to its learning. However, the evaluation feature has not been facilitated on the web. While in the educational process, learning evaluation is a factor that needs to be considered to determine the extent to which students master learning and diagnose student learning difficulties. Based on field studies conducted to students at SMK Negeri 4 Bandung, pain points were obtained from their experience in using online-based learning evaluations. Thus, it is necessary to design a User Interface and User Experience (UI/UX) learning evaluation on eCraft2Learn to overcome these pain points using the Design Thinking method. This design is carried out through five stages, namely Empathize, Define, Ideate, Prototype, and Test. With this design, a UI/UX design is produced that can increase students' intrinsic motivation when doing evaluations. Intrinsic motivation is significantly related to the completion of a task. Therefore, the measurement results from user experience through the User Experience Questionnaire (UEQ) are above average, and the UI/UX design that has been designed has a positive effect on the interest or pleasure subscale and the perceived choice subscale.